Effects of milk, pasteurized milk, and milk replacer on health and productivity of dairy calves - Hulbert, Lindsey E; Trombetta, Sophia A.; Noel, Jere A.; Moisa, Sonia J.; Montgomery, Sean P.; Hanzlicek, Greg A.; Bradford, Barry J. (Kansas Agricultural Experiment Station and Cooperative Extension Service, 2015)
Our objectives were to determine the health and blood parameters before, during, and after weaning of 114 Holstein heifers fed either accelerated milk replacer (MR; 28% CP, 18% fat) or non-saleable milk (3.59 ± 0.28% true protein; 4.12 ± 0.37% fat) that was either pasteurized (PM) or raw (RM; refrigerated and fed <24 h after collection). Calves were randomly assigned to feeding treatments at birth. Colostrum (1 L) was fed less than 14 hours after birth (MR and PM = pasteurized colostrum; RM = raw colostrum). All calves were bottle-fed 1.8 ± 0.20 L, 3 times daily; all calves were provided fresh water and grain ad libitum throughout the experiment. Calves began step-down weaning at age 5 weeks and completed weaning at age 6 weeks. Blood samples were collected at ages 3, 5, and 7 weeks and were analyzed for complete blood counts (CBC) using a Procyte Idexx Analyzer (IDEXX Laboratories, Inc., Westbrook, ME). Fecal scores were observed twice daily, on a 1 to 3 scale (FS1 = normal, FS2 = loose, FS3 = scours). Results showed that MR-fed calves had more (P < 0.01) observations (%obs) with FS > 2 than the PM- and RM-fed calves (2.3 vs. 1.6 and 1.7 ± 0.2 %obs, respectively). In addition, there were no differences in body weight or shoulder or hip height between treatments, but a treatment × week interaction (P = 0.05) occurred for grain consumed, with a noticeably higher increase between 6 and 7 weeks of age for MR calves. When CBC was considered, there were no differences in blood cell types, but MR-fed calves had greater mean corpuscular volume (MCV) than the other calves (P < 0.01), leading to higher resistance for iron deficiency anemia. In conclusion, these findings suggest that calf performance and feed intake are not affected by the administration of raw milk, pasteurized milk, or milk replacer. Moreover, CBC health parameters showed no significant changes due to administration of the different types of milk sources.
Dairy Research, 2014 is known as Dairy Day, 2014
Keywords: Milk replacer; Pasteurization; Calves; Hematology; Fecal score